2021
DOI: 10.32014/2021.2518-170x.113
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic Field Transforms and Their Interpretation at Exploration for Hydrocarbon Field in the Southern Part of the Ustyurt Region

Abstract: E d i t o r i n c h i e f ZHURINOV MuratZhurinovich, doctor of chemistry, professor, academician of NAS RK, president of the National Academy of Sciences of the Republic of Kazakhstan, general director of JSC "Institute of fuel, catalysis and electrochemistry named after D.V. Sokolsky» (Almaty, Kazakhstan) H = 4 E d i t o r i a l b o a r d: ABSAMETOV Malis Kudysovich, (deputy editor-in-chief), doctor of geological and mineralogical sciences, professor, academician of NAS RK, director of the Akhmedsafin Institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The same trend is observed in all other counties with low hazard exposure, with the exception of Kukes (74% and 68% of PHPHigh in Vlore and Shkoder, and only 24% in Kukes). Actually, moderate to high correlations between FWI values and fires occurrence have been found in many studies [7][8][9]. These results contradict the abovementioned studies, but it can be concluded that vigilance and awareness in these communities appear to be low due to the low frequency of fires in these prefectures.…”
Section: Four-level Hazard Exposure Analysismentioning
confidence: 81%
“…The same trend is observed in all other counties with low hazard exposure, with the exception of Kukes (74% and 68% of PHPHigh in Vlore and Shkoder, and only 24% in Kukes). Actually, moderate to high correlations between FWI values and fires occurrence have been found in many studies [7][8][9]. These results contradict the abovementioned studies, but it can be concluded that vigilance and awareness in these communities appear to be low due to the low frequency of fires in these prefectures.…”
Section: Four-level Hazard Exposure Analysismentioning
confidence: 81%
“…Such a picture is evidence in favor of the fact that this depression is completed by rocks with low thermophysical properties and relatively isotropic in its geological structure. The latter is related to the minimal values of the Bouguer anomaly horizontal and vertical gradient module transforms, local negative gravity anomalies (recalculated in the upper half-space at a height of 2.5 km), autotrace of the axes of theТа magnetic field anomalies, reduced values of TDR transform (Abetov and Yessirkepova and Curto, 2021), (Table 1). Map of the thermal field recalculated in the lower half-space.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence in favor of the completion of this depression by rocks with low thermophysical properties and a relatively isotropic geological structure is supported by the following: minimal values of the Bouguer anomaly horizontal and vertical gradient module transforms, local negative gravity anomalies (recalculated in the upper half-space at a height of 2.5 km), autotrace of the axes of the ΔТа magnetic field anomalies, and reduced values of TDR transformant [4,14].…”
Section: Assakeaudan Depressionmentioning
confidence: 92%
“…The upper edge of the causative magnetic masses drops to a depth of 8-10 km, which corresponds to the depths of the basement rocks (according to seismic CDP-2D) and reflects the level of maximum propagation of basic and ultrabasic rocks into the basement [14].…”
Section: Assakeaudan Depressionmentioning
confidence: 98%
See 1 more Smart Citation